Intervención fisioterapéutica en paciente masculino de 43 años post-quirúrgico de ligamento cruzado anterior y posterior de rodilla izquierda. - Gómez Pucha, Nathaly Nayelhy (2024)
The present clinical case focused on the physiotherapeutic intervention for a 43-year-old male patient, post-surgery for the reconstruction of the ACL and PCL in the left knee. The main objective was to determine the effectiveness of the treatment by considering his personal data, pathological history, clinical background, and reason for consultation, thereby exploring various treatment approaches. The initial evaluation in primary care allowed for the formulation of presumptive, definitive, and physiotherapeutic diagnoses, which enabled the treatment to be adjusted according to the patient’s individual response and requirements for optimal rehabilitation. During the initial weeks, lymphatic drainage and muscle activation were prioritized, followed by improvements in joint range of motion and strengthening with resistance bands in the intermediate phases. Finally, the intervention progressed to gait re-education, first with assistance and then without technical aid, complemented by proprioceptive exercises. The results showed a significant reduction in edema, improvements in the range of motion, and functional recovery of gait.